Fish quarantine and fish diseases in South and Southeast Asia 1986 Update. - Arthur, J. R. (ed.). (Manila, Philippines Asian Fisheries Society, 1987)
Asian Fisheries Society Special Publication No. 1
Keywords: Fishes Diseases; Fisheries